The role of sphingosine kinase 1/sphingosine-1-phosphate pathway in the myogenic tone of posterior cerebral arteries. - Mihwa Lim (Public Library of Science (PLoS), 2012)
Aims The goal of the current study was to determine whether the sphingosine kinase 1 (SK1)/sphingosine-1-phosphate (S1P) pathway is involved in myogenic vasoconstriction under normal physiological conditions. In the present study, we assessed whether endogenous S1P generated by pressure participates in myogenic vasoconstriction and which signaling pathways are involved in SK1/S1P-induced myogenic response under normal physiological conditions. Methods and results We measured pressure-induced myogenic response, Ca(2+) concentration, and 20 kDa myosin light chain phosphorylation (MLC(20)) in rabbit posterior cerebral arteries (PCAs). SK1 was expressed and activated by elevated transmural pressure in rabbit PCAs. Translocation of SK1 by pressure elevation was blocked in the absence of external Ca(2+) and in the presence of mechanosensitive ion channel and voltage-sensitive Ca(2+) channel blockers. Pressure-induced myogenic tone was inhibited in rabbit PCAs treated with sphingosine kinase inhibitor (SKI), but was augmented by treatment with NaF, which is an inhibitor of sphingosine-1-phosphate phosphohydrolase. Exogenous S1P further augmented pressure-induced myogenic responses. Pressure induced an increase in Ca(2+) concentration leading to the development of myogenic tone, which was inhibited by SKI. Exogenous S1P further increased the pressure-induced increased Ca(2+) concentration and myogenic tone, but SKI had no effect. Pressure- and exogenous S1P-induced myogenic tone was inhibited by pre-treatment with the Rho kinase inhibitor and NADPH oxidase inhibitors. Pressure- and exogenous S1P-induced myogenic tone were inhibited by pre-treatment with S1P receptor blockers, W146 (S1P1), JTE013 (S1P2), and CAY10444 (S1P3). MLC(20) phosphorylation was increased when the transmural pressure was raised from 40 to 80 mmHg and exogenous S1P further increased MLC(20) phosphorylation. The pressure-induced increase of MLC(20) phosphorylation was inhibited by pre-treatment of arteries with SKI. Conclusions Our results suggest that the SK1/S1P pathway may play an important role in pressure-induced myogenic responses in rabbit PCAs under normal physiological conditions.